Identification of host factors for livestock and poultry viruses: genome-wide screening technology based on the CRISPR system - Hu, Shijie; Gan, Mailin; Wei, Ziang; Shang, Pan; Song, Lei; Feng, Jinkang; Chen, Lei; Niu, Lili; Wang, Yan; Zhang, Shunhua; Shen, Linyuan; Zhu, Li; et al. (Frontiers in Microbiology, 2024)
Genome-wide CRISPR library screening technology is a gene function research tool developed based on the CRISPR/Cas9 gene-editing system. The clustered regularly interspaced short palindromic repeats/CRISPR-associated genes (CRISPR/Cas) system, considered the third generation of gene editing after zinc finger nucleases (ZFN) and transcription activator-like effector nucleases (TALEN), is widely used for screening various viral host factors. CRISPR libraries are classified into three main categories based on the different functions of Cas9 enzymes: CRISPR knockout (CRISPR KO) library screening, CRISPR transcriptional activation (CRISPRa) library screening, and CRISPR transcriptional interference (CRISPRi) library screening. Recently, genome-wide CRISPR library screening technology has been used to identify host factors that interact with viruses at various stages, including adsorption, endocytosis, and replication. By specifically modulating the expression of these host factors, it becomes possible to cultivate disease-resistant varieties, establish disease models, and design and develop vaccines, among other applications. This review provides an overview of the development and technical processes of genome-wide CRISPR library screening, as well as its applications in identifying viral host factors in livestock and poultry.